Vitamin C–Based Gingival Depigmentation Versus Surgical Depigmentation: A Randomized Clinical Trial - Aehad Ul Haque; Nand Lal; Shalini Kaushal; Pavitra Rastogi; Rameshwari Singhal (The Scientific World Journal)
Conclusion: Based on the findings of this study, it was concluded that locally injected vitamin C and surgical depigmentation are comparable in their effectiveness for treating gingival hyperpigmentation.